The Milk Compositions and Blood Parameters of Lactating Dezhou Donkeys Changes With Lactation Stages - Miaomiao Zhou; Zongjie Ma; Xinyi Du; Changfa Wang; Guiqin Liu (Veterinary Medicine and Science)
ABSTRACT The aim of this study was to investigate the changes in milk compositions and blood parameters of Dezhou donkeys during the lactation. Milk and serum samples from six lactating Dezhou donkeys were collected at 1, 30, 60, 90, 120, 150 and 180 days of lactation. The results displayed that the milk yield during the lactation first increased and then gradually decreased, with the peak milk production period of 30–60 days after parturition. Compared with other lactation stages, milk fat, milk protein, milk solids and solids non‐fat (SNF) were higher in early lactation (p < 0.05). Conversely, the milk of late lactation stage had a higher lactose content (p < 0.05); The mineral elements content in donkey milk decreased with the prolongation of lactation period (p < 0.05); The blood serum prolactin (PRL), insulin‐like growth factor 1 (IGF‐1), total protein (TP), albumin (ALB), glucose (GLU), total cholesterol (TG), triglyceride (TC), alkaline phosphatase (ALP), lactate dehydrogenase (LDH), high density lipoprotein (HDL) and low density lipoprotein (LDL) were higher in early lactation stage (p < 0.05), similar to changes in milk compositions during lactation. The correlation analysis results showed that the milk yield was positively correlated with PRL, IGF‐1 and ALP, and negatively correlated with ALB (p < 0.05); the milk composition, such as milk fat, protein, solids and SNF were positively correlated with blood GLU, LDH, TP, ALB, TC, TG, HDL and LDL (p < 0.05). The above results indicated that the lactation stage had significant effects on milk production, milk composition, blood biochemical indicators and hormone of lactating donkeys. This study investigated the changes of Dezhou donkeys’ milk performance and blood parameters with lactation stages for the first time, which may contribute to the exploration of the nutritional value of donkey milk and provide theoretical support for the nutritional regulation and utilisation of donkey milk.